Implementasi Low Power Pada Sistem Pemantau Lahan Pertanian Berbasis Komunikasi MRF24J40MA - Ahmad Ghufron Agustian; Mochammad Hannats Hanafi Ichsan; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Agriculture has now been transformed using a variety of technologies to increase production. Traditional agriculture has shifted to smart farming that utilizes the Internet of things using Wireless Sensor Network (WSN) as an information gathering and monitoring control application. The 802.15.4 protocol based agricultural land monitoring system has reliability in monitoring and sending data, this system runs for a long time, so an effort is needed to save energy in the system using the Low Power method so that the use of resources is reduced. In applying the Low Power method use the sleep mode powerdown feature which will forcibly turn off some work functions from ATmega328P. In the implementation of this system 3 Nodes are used, among others: 2 End Devices that perform data retrieval and delivery, and 1 PAN Coordinator as a server or data receiver. The test results using the Low Power method get savings of an average of 6 mA or 12.7%, namely the average value of the current when the system wake is 47.7 mA and when sleep is 42.3 mA. In addition, based on packet loss testing, data transmission is obtained at the optimal distance of 25 meters between End Device and PAN Coordinator.